ANALISA JOINT ERECTION KONSTRUKSI BAJA BLOCK B05 & B07 KAPAL PATROLI POLISI 63 METER DENGAN MOBILE CRANE 72.000 TON - Khristyson, Samuel Febriary; Leksono, Suryo Hadi (Jurnal Proyek Teknik Sipil, 2020)
The construction of modern vessels is already different from traditional ships, modern vessels are usually constructed by block methods where the ship is constructed from the pieces and starts from the centre piece. The construction with this method was used on the police patrol ship 63m . The process of unification of the block was done after the block was finished through the assembly process and also passed several parameters, the parameters that must be achieved and implemented before the process of the joint erection is the identification of the material, scantling Check, welding check, dimension check, readiness of the crane, building berth, number of boat blocks, and Indetification Risk. In the implementation of the block construction unification process using the help of the crane and the Trailer to move the blocks from the jig table to the building birth. The selection of the crane itself is based on the block load, being for the number of eye plates when the joint erection depends on the number and capacity of the crane used. And in this case the load of each eye plate is 35.26 kN and maximum stress 376,30 Mpa  in block B05 and then 23, 51 kN in and maximum stress  313,30 Mpa in  block B07. After the joint erection is still needed to be checked, the things to be checked are dimensional check, plate and member flatness, member straightness, Visual weld inspection, and non-destructive test according to WPS.